Relation of Religion, Economy, and Constitution in the Structure of State Life - Syarifah Gustiawati Mukri; Ahmad Mukri Aji; Nur Rohim Yunus (STAATSRECHT: Indonesian Constitutional Law Journal, 2017)
Abstract:Religion is the main foundation in the fabric of human life. Without religion, humans do not have guidelines in their lives. However, economic dominance in life often triggers people to forget religion as a guide to their life. As a result, religion is denied, antagonized, even considered as a trigger for poverty of the community. It is not surprising then that several countries in their order of state of life have eliminated aspects of religion in their constitution. In this study using a sociological normative approach and qualitative studies in several literatures. The final conclusion, the authors get a relationship between religion, economics and the constitution in the order of state life.Keywords: Religion, Economy, Constitution Abstrak:Agama merupakan landasan utama dalam tatanan kehidupan manusia. Tanpa agama, manusia tidak memiliki pedoman dalam kehidupannya. Namun, dominasi ekonomi dalam kehidupan sering malah memicu manusia melupakan agama sebagai pedoman hidupnya. Sehingga akibatnya agama dinafikkan, dimusuhi, bahkan dianggap sebagai pemicu kemiskinan warga masyarakat. Tak heran bila kemudian beberapa negara dalam tatanan kehidupan bernegaranya menghilangkan aspek agama dalam konstitusinya. Dalam penelitian ini menggunakan pendekatan normatif sosiologis dan studi kualitatif pada beberapa literatur. Kesimpulan akhir, penulis mendapatkan adanya hubungan antara agama, ekonomi dan konstitusi dalam tatanan kehidupan bernegara. Kata Kunci: Agama, Ekonomi, Konstitusi